Maintaining storability of shelled rubber (Hevea brasilliensis, Muell - Arg) seed using potential osmotic solution and fungicide - . Charloq; Zulkifli Lubis; Tumpal H. Siregar (Syiah Kuala University, 2012)
Rubber seed will loose its storability in a short time. Seed germination and fungal attack were factors that barrier the storage period. The research aim was to test the ability of the potential osmotic solution and fungicides to reduce seed germination. Completely randomized design with two factors and three replications, i.e: PEG 6000 (w/v): 0%, 15%, 30%, 45%, 60% (potential osmotic solution) and fungicide (active ingredients were pyraclostrobin + metiram ) (g / 1 kg seed): 0 g, 10 g, 20 g, 30 g and 40 g, were applied.The results showed that PEG 30% can inhibit seed germination up to 9.07% and 37.47% and fungicides 40 g/1kg can reduce fungal attack during storage of 12 and 16 days. Combination of PEG-6000 30% and fungicides 40g / 1 kg could maintain seed storability by pressing the seeds germination up to 10.67% and fungal attacks up to 18.00% during storage of 16 days with 96.80% germination.